THE EFFECT OF ADDITION PROBIOTIC EM4 (Effective microorganism) IN FEED ON GROWTH AND SURVIVAL RATE OF THE DAMSELFISH (Anabas testudineus) WITH AKUASIMBER SYSTEM - Septi Antika; Usman M Tang; Iskandar Putra (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
This research aimed to obtain the The Effect of Addition Probiotic EM4 (Effective microorganism) inFeed on Growth and Survival Rate of the Damselfish with Akuasimber System. The method in thisresearch used a Completely Randomized Design (CRD) of one factor consisting of four levels, thetreatment applied was the addition of probiotics with different doses, namely: 0 ml / kg of feed, 10 ml / kgof feed, 15 ml / kg of feed, and 20 ml / kg of feed. The Damselfish used was 3-5 cm. The feed used is acommercial pellet, namely PF-800, given as much as 5% of the body weight of betok fish which is addedwith probiotics according to the probiotic dose, dissolved with water where the amount of solvent waterused is 30% of the total feed weight and molasses 0.1 ml / g, after the mixture is homogeneous, themixture of probiotic EM4 is put into a sprayer to be evenly sprayed onto the feed, the feed that has beensprayed with probiotics is dried and ready to be given to the test fish. The results of this research showed aprobiotic dose of 20 ml / kg of feed of specific growth of 2.68%, absolute weight of 3.32 grams, absolutelength of 2.07 cm, feed efficiency of 60.73%, feed conversion of 1.64. , blood glucose 98.34 mg / dL, andsurvival rate of 100%.